Police officer perceptions of harassment in England and Scotland - Sheridan, Lorraine; Scott, A.; Nixon, K. (John Wiley & Sons Ltd., 2014)
Purpose: Research has demonstrated that certain relational biases exist within perceptions of stalking. One such bias concerns the perception that ex-partner stalkers are less dangerous than those who target strangers or acquaintances despite applied research suggesting the opposite. Method: In all, 135 police officers in England (where stalking has been outlawed since 1997) and 127 police officers in Scotland (where stalking has been outlawed since 2010) responded to vignettes describing a stalking scenario in which the perpetrator and victim were portrayed as strangers, acquaintances, or ex-partners. Results: Although typical relational biases existed in both samples, Scottish police officers were less susceptible to these biases than English police officers. Victim responsibility mediated the relation between prior relationship and perceptions of stalking for the English, but not the Scottish, police officers. Conclusions: Future work should examine whether these biases may be found in other areas of the criminal justice system, and how far they are influenced by policy, practice, and training.